2018
DOI: 10.1016/j.addr.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing albumin as a carrier for cancer therapies

Abstract: Serum albumin, a natural ligand carrier that is highly concentrated and long-circulating in the blood, has shown remarkable promise as a carrier for anti-cancer agents. Albumin is able to prolong the circulation half-life of otherwise rapidly cleared drugs and, importantly, promote their accumulation within tumors. The applications for using albumin as a cancer drug carrier are broad and include both traditional cancer chemotherapeutics and new classes of biologics. Strategies for leveraging albumin for drug d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
371
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 456 publications
(372 citation statements)
references
References 132 publications
(141 reference statements)
1
371
0
Order By: Relevance
“…The previously determined crystal structure study of HSA revealed that the protein consists of three homologous domains (I‐III), and each domain has two subdomains (A and B) . Many commonly used drugs with acidic or electronegative features bind to subdomains IIA and IIIA . The docking results showed that IR820 binds to subdomain IIA of HSA (Figure a).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The previously determined crystal structure study of HSA revealed that the protein consists of three homologous domains (I‐III), and each domain has two subdomains (A and B) . Many commonly used drugs with acidic or electronegative features bind to subdomains IIA and IIIA . The docking results showed that IR820 binds to subdomain IIA of HSA (Figure a).…”
Section: Resultsmentioning
confidence: 92%
“…HSA is an abundant plasma protein in the blood and tissue fluids, and it can covalently or noncovalently attach to reporting molecules. HSA‐based probe design has shown to be a very useful and powerful strategy for developing molecular probes for theranostic treatment of diseases, especially for tumors with natural passive albumin accumulation . In this study, based on the fact that IR820 has structural similarity to ICG as well as two sulfonic acid groups, we hypothesize that it may bind to HSA, and the resulting IR820–HSA protein complex can be effectively used for NIR‐II imaging.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast to previously reported oxygen‐irrelevant phototherapeutic agents, the present BIA NPs do not employ any inorganic/metallic carriers or photothermal agents. The use of FDA‐approved ICG and albumin‐based drug delivery systems exhibit several outstanding merits including inherent biocompatibility, long blood circulating time, and ease of mass production, showing remarkable preclinical and clinical promises …”
Section: Introductionmentioning
confidence: 99%